Adam in the garden and Lear in the storm: the human amidst the animals. Issue 7 (3rd July 2021) - Celermajer, Danielle
ABSTRACT: Amongst humanities scholars seeking to transform our understanding of the relationship between humans and other animals, there is near universal agreement that the stories constitutive of the tradition we call 'the West' assume and inform an ontology of absolute separation and hierarchy, and a politics of domination. Whilst this way of telling stories about our stories elucidates the tremendous hold that the narrative of human/animal discontinuity has, it nevertheless deprives us of resources that might nourish a different way of ordering ourselves and our worlds. By weaving the threads of stories that lie at the heart of our cultural traditions, principally the creation story from the Old Testament, and Shakespeare's King Lear, but also Plutarch's Gryllus, this paper suggests another retelling, one in which the apparent disorder wrought through the loss of human sovereignty opens up to radically different ways of being human and living together with the morethanhuman. If the story of humans' homelessness in the world has, in our historical retellings, also been the occasion for declaring our transcendence and triumph, this paper muses upon how we might story ourselves at home in the world amongst animal others.